2019
DOI: 10.1038/s41598-019-50815-8
|View full text |Cite
|
Sign up to set email alerts
|

Period-3 dominant phase synchronisation of Zelkova serrata: border-collision bifurcation observed in a plant population

Abstract: The population synchrony of tree seed production has attracted widespread attention in agriculture, forestry and ecosystem management. Oaks usually show synchronisation of irregular or intermittent sequences of acorn production, which is termed ‘masting’. Tree crops such as citrus and pistachio show a clear two-year cycle (period-2) termed ‘alternate bearing’. We identified period-3 dominant phase synchronisation in a population of Zelkova serrata. As ‘period-3’ is known to provide evidence to imply chaos in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…The intransitive structure of roshambo has been likened to persistent cycles of species competition in ecological communities, as competitive advantages get traded off among species with no clear winner [ 41 , 42 ]; to the development and stability of species diversity [ 43 , 44 ]; and to the development of high social efficiency in human decision-making [ 45 ]. In ecological contexts, Sakai et al [ 46 ] specifically used the Hilbert transform (a mathematical technique for deriving phase amplitudes) to represent an intransitive three-period stable cycle of ‘masting’ in tree crops, and they further [ 47 ] described how a coffee agroecosystem can constitute a stable dynamic, intransitive situation with the interactions of three elements of an insect pest, parasitoid, and predator. Further, a prime example of an intransitive ecological system was described by Yule and Burns [ 48 ] in New Zealand, who revealed an unexpected additive adverse impact on a native tree species from the reintroducing an insectivore parrot thought to control an herbivorous moth which damages that tree species.…”
Section: Ecological Quantum Bayesian Network In Ecologymentioning
confidence: 99%
“…The intransitive structure of roshambo has been likened to persistent cycles of species competition in ecological communities, as competitive advantages get traded off among species with no clear winner [ 41 , 42 ]; to the development and stability of species diversity [ 43 , 44 ]; and to the development of high social efficiency in human decision-making [ 45 ]. In ecological contexts, Sakai et al [ 46 ] specifically used the Hilbert transform (a mathematical technique for deriving phase amplitudes) to represent an intransitive three-period stable cycle of ‘masting’ in tree crops, and they further [ 47 ] described how a coffee agroecosystem can constitute a stable dynamic, intransitive situation with the interactions of three elements of an insect pest, parasitoid, and predator. Further, a prime example of an intransitive ecological system was described by Yule and Burns [ 48 ] in New Zealand, who revealed an unexpected additive adverse impact on a native tree species from the reintroducing an insectivore parrot thought to control an herbivorous moth which damages that tree species.…”
Section: Ecological Quantum Bayesian Network In Ecologymentioning
confidence: 99%
“…Several researchers have reported that alternate bearing of pistachios do not always exhibit a clear two-year cycle but may feature various types of synchronisations both spatially and annually 20,[36][37][38] . Sakai et al (2019) proposed a practical approach to determine the composition of periodic components of alternate bearing and masting of plant populations 16 . For instance, period-two and period-three sequences are defined as 'ON ⇒ OFF ⇒ ON' and 'ON ⇒ OFF ⇒ OFF ⇒ ON', respectively (see METHODS-Fraction of period section).…”
Section: Spatial Phase Synchronisation Identified In the Orchardmentioning
confidence: 99%
“…A resource budget model (RBM), which is a tent map 18 , has been previously used to model the dynamics of seed production of perennial plant species [7][8][9][12][13][14][15][16][17] . For cross-pollinating species, the global coupled map (GCM) and local coupled map (LCM)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations